Design and experimental study on thermal characteristics of thermal storage flat-plate solar collector. (October 2018) - He, Y T; Yang, J F; Xiao, L X; Yang, Y H
Abstract: A thermal storage flat-plate solar collector is designed to improve working stability of the solar air drying system, which consists of an absorber plate, a transparent cover plate, a heat insulation layer, phase change materials, a tube bank and a shell, etc. The daily thermal characteristics of thermal storage flat-plate air collector system were tested under natural conditions. The results show that heat storage flat-plate solar collector can effectively extend collector heating time, with daily heat efficiency reaching 49.8%, which is 4.6% up as compared to 45.21% of non-thermal storage heat collector.